Incidence and Risk Factors of Polypharmacy in Pediatric Outpatients: A Tertiary Care Analysis - Sara Gillani, Jovaria Saeed, Ghazanfar Mukhtar, Maleeha Saleem, Ahmad Yar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polypharmacy is an emerging concern in pediatric outpatient care, with increasing prevalence due to rising rates of chronic illness, frequent specialist visits, and overlapping prescriptions. Objective: To determine the incidence of polypharmacy among pediatric outpatients and identify key demographic and clinical risk factors associated with it. Methods: This cross-sectional descriptive study was conducted at Sahiwal Teaching Hospital , Sahiwal from February 2022 to July 2022. A total of 125 pediatric outpatients were enrolled in the study using non-probability consecutive sampling. After obtaining informed consent from the parents or guardians, data were collected using a pre-designed, structured questionnaire administered through interviews and review of outpatient prescription slips. Results: The incidence of polypharmacy was found to be 24.8% (n = 31). Polypharmacy was significantly more common in children aged ≥11 years (p = 0.018), those with two or more comorbidities (p < 0.001), and those with ≥3 prior outpatient visits (p = 0.005). The most frequently prescribed medications included antipyretics (70.4%), antibiotics (60%), and antihistamines (51.2%). Multivariate analysis identified age ≥11 years (AOR: 2.65, 95% CI: 1.13–6.21), ≥2 comorbidities (AOR: 5.74, 95% CI: 2.18–15.11), and ≥3 prior visits (AOR: 3.41, 95% CI: 1.42–8.19) as independent predictors of polypharmacy. Conclusion: It is concluded that nearly one in four pediatric outpatients are exposed to polypharmacy, primarily driven by age, multimorbidity, and frequent healthcare utilization. These findings highlight the need for routine medication reviews, coordinated care, and rational prescribing practices to reduce unnecessary drug burden in pediatric populations. Keywords: Polypharmacy, Pediatrics, Outpatients, Risk Factors, Chronic Illness